2013
DOI: 10.1038/eye.2013.144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic anti-glaucoma medications and trabeculectomy on tear osmolarity

Abstract: Purpose To evaluate the tear film osmolarity (TFO) and ocular surface clinical signs and symptoms in chronically medicated glaucoma patients and post-trabeculectomy patients. Methods This is a single-center, prospective case-controlled study. One-hundred and thirty eyes of 130 participants aged Z45 years were included (49 normal controls, 50 glaucoma patients on chronic preserved antiglaucoma medication Z6 months, and 31 post-trabeculectomy patients not on medication Z6 months). TFO, tear break-up time (TBUT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 52 publications
0
38
0
10
Order By: Relevance
“…Results from previous studies have led researchers to speculate on a relationship between OSD and meibomian gland loss and tear dysfunctions, including raised tear film osmolarity after trabeculectomy [5,6,8,30]. If such a relationship does exist, the question remains as to why meibomian gland loss, tear dysfunction, and OSD occur after trabeculectomy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Results from previous studies have led researchers to speculate on a relationship between OSD and meibomian gland loss and tear dysfunctions, including raised tear film osmolarity after trabeculectomy [5,6,8,30]. If such a relationship does exist, the question remains as to why meibomian gland loss, tear dysfunction, and OSD occur after trabeculectomy.…”
Section: Discussionmentioning
confidence: 96%
“…Because meibomian gland secretions prevent water evaporation [11,12], severe meibomian gland loss can induce an increase in water evaporation and tear film hyperosmolarity after trabeculectomy. Since tear film hyperosmolarity leads to ocular surface inflammation and damage [5,[34][35][36], this inflammation may accelerate meibomian gland loss not only in the bleb-contacting areas but also in the bleb-noncontacting areas. However, it should be noted that in our study, we did not analyze tear film osmolarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tear osmolarity was higher in both groups (means 307.0±9.3 and 307.4±11.6mOsm/l, respectively) compared to healthy individuals (mean 301.4 ±7.7mOsm/l). However, no statistically significant differences neither in tear osmolarity nor in BUT and Schirmer's test scores were detected among the three groups (23).…”
Section: Discussionmentioning
confidence: 85%
“…In order to investigate the effects of glaucoma therapy on the ocular surface, Lee and colleagues 41 performed a single-center prospective case-control study including 49 normal control subjects, 50 glaucoma patients on chronic preserved antiglaucoma medications (≥6 months), and 31 posttrabeculectomy patients. They found that both subsets of glaucoma patients had an elevated tear film osmolarity (ORs, 4.43 and 2.76 for medically treated and posttrabeculectomy patients, respectively) and were also more likely to experience dry eye symptoms (ORs, 4.72 and 4.24).…”
Section: Pharmacologic Intraocular Pressure Loweringmentioning
confidence: 99%